1991
DOI: 10.1159/000261380
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Diagnostic and Treatment Decisions of Fissure Caries

Abstract: The purpose of this in vitro study was to test the accuracy and the reproducibility of diagnostic and treatment decisions of fissure caries with and without explorer. 34 dentists were asked to diagnose 61 teeth and decide upon possible treatment. The teeth were then histologically prepared and diagnosed. The agreement between histological and clinical diagnoses was assessed. The results showed no difference in diagnostic accuracy between explorer and visual technique only. Sensitivity (62%) and specificity (84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(111 citation statements)
references
References 8 publications
4
94
0
13
Order By: Relevance
“…Although there are known drawbacks, visual inspection (VI) alone has been claimed to be the best diagnostic method in populations with low caries prevalence, but it is unable to correctly detect caries lesions because of its low sensitivity 12 . On the other hand, the use of a sharp probe along with the visual method does not appear to improve the diagnostic accuracy 16,21 . It may contaminate other sound sites 14 , damage the fissure 3 as well as facilitate the lesion's progression 29 .…”
Section: Introductionmentioning
confidence: 98%
“…Although there are known drawbacks, visual inspection (VI) alone has been claimed to be the best diagnostic method in populations with low caries prevalence, but it is unable to correctly detect caries lesions because of its low sensitivity 12 . On the other hand, the use of a sharp probe along with the visual method does not appear to improve the diagnostic accuracy 16,21 . It may contaminate other sound sites 14 , damage the fissure 3 as well as facilitate the lesion's progression 29 .…”
Section: Introductionmentioning
confidence: 98%
“…Its impact on caries detection and treatment decision making has also been studied by various authors [8][9][10][11][12][13], as it is believed to allow for clearer visualisation of minute defects. However, some of these studies used high magnification values [10][11][12], others [9] have not correlated results with a gold standard [8]. To date there is no study reported which correlates the impact of magnification on visual-tactile detection of caries using ICDAS-II and a CPI-TN probe.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The diagnosis of occlusal caries, especially the noncavitated type, is a difficult and problematic task because of the superficial remineralization potential that can delay cavitation and because of the extensive use of fluorides that can slow the progress of the lesion, strengthen occlusal enamel, and mask dentinal caries. 4,5 In the past decade, numerous studies have been published to improve existing dental caries detection techniques and to seek new noninvasive ones that could quantify the depth of carious lesions.…”
Section: Introductionmentioning
confidence: 99%